Measurement bias in the HICP: what do we know, and what do we need to know? - Mark A. Wynne; Diego Rodriguez-Palenzuela (European Central Bank (ECB), 2002)
The Harmonized Index Of Consumer Prices (HICP) is the primary measure of inflation in the euro area, and plays a central role in the policy deliberations of the European Central Bank (ECB). Among the rationales given for defining price stability as prevailing at some positive measured inflation rate is the possibility that the HICP as published incorporates measurement errors of one sort or another that may cause it to systematically overstate the true rate of inflation in the euro area. The purpose of this paper is to review what is known about the scope of measurement error in the HICP. We conclude that given the scant research on price measurement issues in the EU and the ongoing improvements in the HICP, there is almost no scientific basis at this time for a point (or even an interval) estimate of a positive bias in the HICP.
Keywords: C43; E31; 330; Harmonized Index of Consumer Prices; HICP; measurement error